Towards GDPR-compliant data processing in modern SIEM systems. Issue 103 (April 2021) - Menges, Florian; Latzo, Tobias; Vielberth, Manfred; Sobola, Sabine; Pöhls, Henrich C.; Taubmann, Benjamin; Köstler, Johannes; Puchta, Alexander; Freiling, Felix; Reiser, Hans P.; Pernul, Günther
Abstract: The introduction of the General Data Protection Regulation (GDPR) in Europe raises a whole series of issues and implications on the handling of corporate data. We consider the case of security-relevant data analyses in companies, such as those carried out by Security Information and Event Management (SIEM) systems. It is often argued that the processing of personal data is necessary to achieve service quality. However, at present existing systems arguably are in conflict with the GDPR since they often process personal data without taking data protection principles into account. In this work, we first examine the GDPR regarding the resulting requirements for SIEM systems. On this basis, we propose a SIEM architecture that meets the privacy requirements of the GDPR and show the effects of pseudonymization on the detectability of incidents.